FAKTOR-FAKTOR YANG BERHUBUNGAN DENGANPENGALAMAN IBU DALAM MERAWAT LUKA EPISIOTOMI DI WILAYAH KERJA PUSKESMAS BOTUPINGGE KECAMATAN BOTUPINGGE KABUPATEN BONE BOLANGO - Rheyn R Djunaid; Harismayanti Harismayanti (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Maternal Mortality Rate (MMR) is one indicator to see the health degree of women. The maternal mortality rate is also one of the targets that are set in the millennium development goals (MDG). The targets no. 5 will be achieved in 2015 by improving the women’s health and reducing maternal mortality risk until ¾. The purpose of this study is to determine the factors related to the mother’s Experience in caring their episiotomy wound in the work area of Botupingge Medical Center. The design of study used was descriptive Cros-sectional design. Population and sample were the mothers who brought their children, which were 23 mothers. And according to the formula, the sample taken only 22 mothers. The technique of sampling taken was Aciedental Sampling Technique. Statistical test results obtained by the value p = 0.002 (p <0.05), that meant there was a relationship between the factors affecting the episiotomy wound and the mother’s experience in caring episiotomy wound in the work area of botupingge medical center of botupingge district, bone bolango regency. The result of this study is expected to be a reference of source of episiotomy wound care impact and to be a strategies for nurses and midwives in providing counseling to mothers obut episiotomy wound care.